Asymmetric mass-loss from the white dwarf WD 0253+209 : Secret revealed - Binil Aryal (Bibechana, 2012)
Dust structures around the white dwarf WD 0253+209 is studied in 100 and 60 micron infrared image. These images are received from Infrared Astronomical Satellite Survey (IRAS Survey). The post Asymptotic Giant Branch (AGB) emission of the white dwarf's precursors' wind and the ambient interstellar matter is studied. The distribution of the relative flux density is studied and analyzed in the context of the dust color temperature, mass loading trend and the amount of total mass deposited due the interaction in the interstellar medium. The twisted curved emission structure at 100 micron in the region of interest is probably due to the interaction between the ambient interstellar medium and the He-flashes of the parent planetary nebula of the central white dwarf WD 0253+209. The total mass of the filamentary arc is found to be ~ 5 solar masses, as predicted. The mass loss rate of the post AGB star goes up to 10-5 solar masses per year. It is concluded that the first He-flash occurred at least ~2500 years ago.